Immune cell–intrinsic STING activation drives tumor ferroptosis via AA-mediated suppression of ACSL4 lactylation in colorectal cancer - Lina Ding; Wenqi Du; Jing Zhu; Yuxiang Zhang; Xingyue Wang; Linfeng Li; Buhui Liu; Xiaohong Wang; Qingling Wang; Dongsheng Pei (Proceedings of the National Academy of Sciences, 2026)
Ferroptosis has emerged as a key effector mechanism in antitumor immunity, yet the transcellular metabolic cross talk that modulates ferroptotic sensitivity in colorectal cancer (CRC) remains incompletely understood. Here, we describe an integrative regulatory axis linking immune cell–intrinsic Stimulator of Interferon Genes (STING) signaling to tumor ferroptosis through coordinated lipid metabolism and posttranslational modifications (PTMs). Mechanistically, STING activation in immune cells triggers TANK-binding kinase 1 (TBK1)-dependent phosphorylation of cytosolic phospholipase A 2 (cPLA 2 ) at Ser505, thereby releasing arachidonic acid (AA) into the tumor microenvironment (TME). This immune-derived AA is taken up by adjacent CRC cells, where it promotes ACSL4-dependent ferroptosis by inhibiting EP300-mediated lactylation of ACSL4 at lysine 426 (K426). In vivo, pharmacological activation of STING enhances AA release and facilitates ferroptosis-mediated tumor suppression. Notably, STING agonist synergizes with PD-1 checkpoint blockade to inhibit tumor progression, which is reversed by the ferroptosis inhibitor. Collectively, our findings establish an integrative and transcellular immunometabolic framework linking innate immune sensing to tumor ferroptosis, providing a strong rationale for combinatorial therapeutic strategies in CRC.